2013
DOI: 10.1111/ppe.12070
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about the Natural Outcomes of Preterm Labour? A Systematic Review and Meta‐Analysis of Women without Tocolysis in Preterm Labour

Abstract: Most women without tocolysis do not deliver within 7 days, although the range is very wide. The majority of this variation is unrelated to reported differences in study design or reported population characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(8 reference statements)
0
7
0
4
Order By: Relevance
“…This rate was similar to the rate in studies of preterm labor with cervical dilatation. 20 , 21 The rates of term delivery, birth weight, and neonatal complications between the nifedipine and the placebo groups were not significantly different. These rates were similar to the rates in studies of preterm labor with cervical dilatation.…”
Section: Discussionmentioning
confidence: 82%
“…This rate was similar to the rate in studies of preterm labor with cervical dilatation. 20 , 21 The rates of term delivery, birth weight, and neonatal complications between the nifedipine and the placebo groups were not significantly different. These rates were similar to the rates in studies of preterm labor with cervical dilatation.…”
Section: Discussionmentioning
confidence: 82%
“…This study relied on data from hospital discharge records and birth certificates for analysis. Data were not available to examine other important risk factors for preterm birth (eg, maternal body mass index, 7 income, 25 employment, 26 tocolysis, 27 assisted reproduction, 28 and cervical surgery 29 ). The existing data could not identify elective delivery at 37 and 38 weeks of gestation, which are important points for investigation as this area of work progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two systematic reviews reported [ 16 , 20 ] that applicable data were found, but neither of the systematic reviews used the data. Furthermore, 8 of the reviews did not clearly indicate whether or not data were found [ 17 , 19 , 21 26 ] and it was not possible to determine whether or not the data were used in 1 of the reviews [ 22 ]. In each of these cases, the corresponding cells are marked “yellow”.…”
Section: Resultsmentioning
confidence: 99%